Improving Business Excellence Culture - Dorner, Kevin; Gustafsson, Fredrik (My University, 2023)
With the increasing popularity of Business Excellence (BE) and Lean, many companies have engaged in implementing one or several of these concepts. SKF Gothenburg is one such company that aims to achieve a Lean transformation in the context of a long journey with BE efforts. This history provides the company with both advantages and challenges in its journey towards excellence, hereby creating a unique context for BE. In this qualitative research, a case study of SKF Gothenburg was conducted with an inductive approach. Data was collected through semi-structured interviews with 22 employees, unstructured and semi-structured observations, and review of company documents. Company interviewees spanned a wide range of functions, most of them being functional managers related to the factory management. For improved contextual understanding, interviewees also included some central roles in the SKF Group organization, as well as factory employees with supportive, and more operational roles. Based on the company’s needs, and the identified gaps in literature, two research questions were formulated. Through these questions, the challenges with the current Business Excellence culture have been identified, and improvements have been suggested. Problematic areas were linked to four topics. The first improvement area was the implementation approach and organizational context of the company’s Lean implementation through the SKF Production System. Related to this was also the company’s approach towards strategy creation and deployment. Furthermore, people related aspects were found to be in need of improvement regarding the state and management of knowledge, motivation, culture, and collaboration. Leadership was the last identified improvement area, where issues with prioritization, leadership style, and ownership were described. For these areas, improvement suggestions were derived from the current literature in related scientific fields. Suggestions regarding the SPS implementation were related to increasing the understanding, ownership, and improving the clarity of the vision. Hoshin Kanri implementation, as well as improved communication and visibility of the strategy were suggested to improve strategy aspects. To improve people related aspects, better training, increased cross-functional collaboration and knowledge sharing, and improved HR approaches were suggested. Lastly, to address leadership improvements, it was suggested to increase knowledge and use of transformational and lean leadership, to improve focus on proactiveness and continuous improvement, and to increase the time spent with strategic matters. Through this report, SKF Gothenburg can reach a better understanding regarding issues with its BE culture. These issues, as well as their implications, were well-described based on the collected data. The high variety of the potential areas for improvements identified were addressed with a multifaceted literature review, whereby appropriate solutions or approaches towards developing solutions have been suggested.
Keywords: Business Excellence; EFQM; Employee Engagement; Hoshin Kanri; Intrinsic Motivation; Lean; Organizational Learning; Transformational Leadership